Regulation of Sidewalk Use in Response to the Rise of Street Coffee Businesses in Cilacap Regency (Indonesian Journal of Agrarian Law, 2026)
The use of sidewalks by street coffee businesses in Cilacap Regency has grown as part of microeconomic activity, but has the potential to disrupt public peace and order if not properly regulated. This study aims to describe the existence and use of sidewalks by street coffee businesses, as well as to analyze the regulatory measures taken by the local government in response to the proliferation of these businesses. The research questions in this study are: (a) What is the current state of the existence and use of sidewalks by street coffee businesses in Cilacap Regency? (including photos, data, interviews, and patterns of sidewalk use); (b) How are enforcement measures regarding sidewalk use in response to the proliferation of street coffee businesses implemented? (including the meaning of enforcement, legal basis, implementing agencies, the intended function of sidewalks, and implicit obstacles that arise). The research method employed is a socio-legal approach using a legislative and descriptive-analytical framework, supported by literature review, interviews, and field observations. The research findings indicate that regulation has been implemented through data collection, guidance, and enforcement actions by relevant authorities; however, its effectiveness has not yet been maximized. This is due to limited regulatory resources and infrastructure, weak interagency coordination, and the absence of detailed technical regulations regarding zoning and permits for sidewalk use. Therefore, it is recommended that clear technical regulations regarding zoning be established, inter-agency coordination be improved, and participatory guidance be strengthened.